Technology-based comparative life cycle assessment for palm oil industry: the case of Nigeria - Kelechi E. Anyaoha; Lulu Zhang (Environment, Development and Sustainability, 2022)
Oil palm dominates global oil production, trade, and consumption. Nigeria is one of the leading palm oil producers and consumers. A significant challenge of the palm oil industry is to reduce the environmental impacts (e.g. pollution and carbon footprint) and integrate a circular economy in operation. This study aims to comparatively quantify the environmental impacts of technologies used by different mills. We applied a life cycle assessment in the case of Nigeria. The study covers the reception and processing of fresh fruit bunch (FFB) to end-product palm oil. The inputs include generated empty fruit bunch (EFB), mesocarp fibre, palm kernel shell, palm oil mill effluent, diesel, water and all outputs to the environment for a functional unit of 1-tonne FFB. The results showed that large-scale mills perform worse (468~kg CO2-eq per t FFB) than the semi-mechanised and smallholder mills in effects on climate change but better in the other impact categories, including human toxicity, ecotoxicity, and fine particulate matter formation. In large-scale mills, the climate change impacts decrease by 75% when the raw palm oil mill effluent (POME) is used in composting EFB. Similarly, climate change impacts reduce by 44% when biogas from POME substitutes diesel in the semi-mechanised and smallholder mills. We conclude that regulatory measures are needed to ensure improved management practices in the production processes. Particular attention should be paid to the generation and reuse of biomass and POME. This study provides a handy reference to assist the sustainable energy transition in Nigeria's and other parts of sub-Saharan Africa's oil palm industry to mitigate climate change and form a cleaner bioeconomy.
Keywords: 330; Life cycle assessment; Environmental impact; Climate change mitigation; Circular economy; Fresh fruit bunch